Exploring the Role of FDG PET CT Scan in Detecting High Grade Diffuse Large B-Cell Lymphoma - Marzieh Azmoun; Mohammad Moeini Nodeh; Maryam Emadzadeh; Kamran Ariana; Habibollah Dadgar; Amirreza Khorosanchi; Emran Askari; Eisa Nazar (Архивъ внутренней медицины, 2025)
Introduction. Diffuse B-cell lymphoma (DLBCL) is the most common type of non-Hodgkin’s lymphoma. Currently, the standard method for evaluating patients at the initial stages of cancer diagnosis in Mashhad oncology centers involves computed tomography scans (CT scans), histopathological evaluation of tissue, bone marrow sampling, and cytogenetic studies, all of which are time-consuming and costly. It is worth mentioning that at present, the most recommended approach for determining lymphoma staging is the FDG-PET/CT scan, which combines labeled glucose with CT scan and offers a more accurate alternative. The objective of this study is to explore the potential of FDG-PET/CT scan as a tool for detecting high-grade lymphoma.Methods. In this study, patients with different types of DLBCL who underwent FDG-PET Scan for staging at Razavi Hospital, Mashhad, Iran between 2017 and 2021 were examined. The necessary clinical and paraclinical information, including the stage of the disease, the involved site at the time of diagnosis, the result of immunohistochemical examination, and the response to treatment were collected. FDG-PET Scan information including the extent of involvement and metabolic activity of the tumor before the start of treatment, pathological characteristics of the tumor, clinical behavior, and response to treatment in the form of response rate (RR), disease-free survival (DFS) and overall survival (OS) of the patients. Was also investigated. Aggressive histology in the present study was classified based on morphological characteristics and immunohistochemical staining, prognostic indicators, clinical behavior and response to treatment. Data were analyzed using SPSS software at a significance level of p<0.05.Results. Comparing the two groups of patients with high grade histology (n=12) and NOS (n=14), the results showed that SUV max values in patients with aggressive lymphoma were 27.5 ± 15.6 (median 25.6) and in patients with NOS lymphoma was 15.4 ± 9.8 (median 14.4) (p=0.01). The overall survival of patients in the aggressive group was 10 months and in the non-aggressive group was 24 months (p=0.002). Also, the cut — off -point of 21.1 for SUV max has a sensitivity of 66 % and a specificity of 72 % in differentiating aggressive from non-aggressive types.Conclusion. The results revealed that FDG PET CT Scan can provide valuable insights into differentiating lymphomas with a more aggressive type from their usual types, as those with heightened metabolic activity (SUVmax) are often indicative of aggressive behaviors.